Non-Computerised Cognitive Remediation Improves Cognitive Function And Reduces Serum Tumour Necrosis Factor Alpha (Tnf-A ) Levels In Schizophrenia Patients Treated With Risperidone At Rskd Dadi Makassar In 2024 - Akbar, Arvita Revianty; Tanra, A.Jayalangkara; Liaury, Kristian; Bahar, Burhanuddin; Teddy Lisal, Sonny; Azis, Ilhamuddin; Syamsuddin, Saidah (Journal of Neonatal Surgery, 2025)
Background: Schizophrenia is a chronic mental disorder that affects millions of people worldwide. In Indonesia, its prevalence increased from 1.3 to 6.7 per 1,000 households between 2013-2018. Cognitive impairment, especially episodic memory deficits, is a major predictor of poor outcome, associated with dysfunction of brain circuits such as the dorsolateral prefrontal cortex and hippocampus. Inflammation, particularly through TNF-α, plays an important role in the pathogenesis of these cognitive impairments. Objective: The purpose of this study was to determine the effect of cognitive remediation on the improvement of cognitive symptoms and serum TNF-a levels of schizophrenia patients who received risperidone therapy. As well as knowing the correlation between cognitive symptoms and serum TNF-a levels in schizophrenia patients in Makassar, Indonesia. Methods: This experimental study examined 40 male schizophrenia patients at Dadi Regional Special Hospital, randomly divided into treatment (risperidon + cognitive remediation) and control (risperidon alone) groups. Conducted in September-October 2024, TNF-α levels were measured by ELISA, while cognitive function was assessed using SCORSVI. Results: Both groups showed significant cognitive improvement, but better in the risperidone + cognitive remediation group. Serum TNF-α levels decreased significantly after 8 weeks, with a greater decrease in the treatment group. Spearman test showed a significant positive correlation between serum TNF-α and cognitive dysfunction (r=0.884; p=0.001). Conclusion: We found that non-computerised cognitive remediation in schizophrenia patients receiving risperidone therapy can provide better improvement in cognitive dysfunction compared with no cognitive remediation. There was also a correlation between serum TNF-a levels and improvement in cognitive symptoms (SCORSVI score) in both groups, where the lower the SCORSVI score, the lower the serum TNF-a levels.